Explorando a climatologia : uma experiência de iniciação científica com alunos do ensino médio - Padilha, Rinaldo Marques (2024)
Reflections on scientific initiation in basic education have been widely disseminated in the academic field, promoting the expansion of the concept of scientific literacy and contributing to the improvement of teaching and learning processes in the country. Although there are numerous junior scientific initiation projects in Brazil, most basic education schools have not had opportunities to develop such research projects with their students, which can also be observed in the municipality of Colíder. In relation to climatology, especially urban climate, there are no studies on the subject, highlighting a gap to be filled. This work presents a scientific initiation project in basic education, which can serve as an alternative for schools that were not funded by public funding agencies. A research project was developed involving high school students, who produced meteorological instruments using low-cost alternative materials to be used as learning resources. The research is based on an investigative approach of a qualitative nature, relying on diverse evidence sources and methods of data collection. Most of the equipment used are materials that students already have at home, such as PET bottles, glass jars, balloons, straws, alcohol, etc. These instruments promoted a better understanding by students of the concepts of climate and weather, as well as methods for collecting data to characterize the climate of a specific location. The students also built automatic weather stations using Arduino and low-cost sensors to monitor climate variables in the municipality of Colíder. They monitored and diagnosed urban heat islands through mobile transects in the urban area of the municipality. As a result of the scientific initiation activities, they participated in a state scientific fair, producing a weather station, as well as producing and publishing a research abstract in the event's Proceedings. They monitored and analyzed air temperature and rainfall data at the school over a period of 12 months. The research results indicate that there were significant knowledge gains, according to the Theory of Meaningful Learning, with students understanding fundamental climatology concepts, developing skills in producing data collection instruments for meteorological data, analyzing atmospheric phenomena, and producing and publishing articles in scientific journals, engaging in scientific initiation as young researchers.